Assessment of the in vitro genotoxicity of TiO2 nanoparticles in a regulatory context. Issue 4 (21st April 2018) - Charles, Sandrine; Jomini, Stéphane; Fessard, Valérie; Bigorgne-Vizade, Emilie; Rousselle, Christophe; Michel, Cécile
Abstract: A review of in vitro genotoxicity studies on titanium dioxide nanoparticles (TiO2 -NPs) published between 2010 and 2016 was performed by France in the framework of the CLP Regulation 1272/2008/EC. Neither the few in vivo studies of low quality nor the larger number of acceptable in vitro studies available for genotoxicity allowed France to conclude on the genotoxicity of TiO2 -NPs. Based on this work, it was decided to compare the acceptable in vitro studies to understand the reasons for the diverging results observed, such as the materials tested or of the protocols used and their inherent interferences. The systematic review performed on in vitro genotoxicity data for TiO2 -NPs was then restricted to studies with the highest level of confidence among studies following OECD guidelines and the largely applied comet assay. Indeed, the aim of this article is to understand why, even if judged of good quality, the 36 publications selected and analyzed did not lead to a clear picture. Some recommendations to be taken into account before performing new in vitro genotoxicity assays for insoluble particles such as TiO2 -NPs are proposed. Although secondary genotoxic effects consequent to oxidative stress seem to be the major mechanism responsible for the genotoxicity of TiO2 -NPs reported in some studies, primary genotoxic effects cannot be excluded. Further studies are needed to clarify the exact mode of action of TiO2 -NPs and to highlight which physicochemical properties lead to their genotoxicity in vitro to ultimately identify a specific combination of parameters that could represent a risk in vivo.